Concomitant transformation to multiple myeloma and acute biphenotypic leukemia from MGUS simultaneously diagnosed with essential thrombocythemia 37-years before. - Pasquale Niscola (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract. The association of monoclonal gammopathy of undetermined significance (MGUS) with essential thrombocytopenia (ET) in the same patient is quite rare. With an anecdotal purpose, we herein report the long-lasting clinical history of an our patient who presented the simultaneous evolution to multiple myeloma (MM) and to acute biphenotypic leukemia from MGUS and ET respectively, have been the latter conditions simultaneously diagnosed 37 years before.